Fast In-House Next-Generation Sequencing in the Diagnosis of Metastatic Non-small Cell Lung Cancer: A Hospital Budget Impact Analysis - Ubong Silas; Maximilian Blüher; Antonia Bosworth Smith; Rhodri Saunders (Journal of Health Economics and Outcomes Research, 2023)
# Background Targeted therapy for cancer is becoming more frequent as the understanding of the molecular pathogenesis increases. Molecular testing must be done to use targeted therapy. Unfortunately, the testing turnaround time can delay the initiation of targeted therapy.